2013
DOI: 10.1530/jme-12-0200
|View full text |Cite
|
Sign up to set email alerts
|

TSH induces metallothionein 1 in thyrocytes via Gq/11- and PKC-dependent signaling

Abstract: Metallothioneins (MTs) are cytoprotective proteins acting as scavengers of toxic metal ions or reactive oxygen species. MTs are upregulated in follicular thyroid carcinoma and are regarded as a marker of thyroid stress in Graves' disease. However, the mechanism of MT regulation in thyrocytes is still elusive. In other cellular systems, cAMP-, calcium-, or protein kinase C (PKC)-dependent signaling cascades have been shown to induce MT expression. Of note, all of these three pathways are activated following the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Previous reports demonstrate that Mt3 mRNA is reduced by thyroxine in the developing rat brain [ 18 ]. Moreover, MT mRNA and protein levels are inducible by thyroid-stimulating hormone (TSH), and their induction is considered a thyroid stress marker of autoimmune diseases [ 52 , 53 ]. Studies in mammals report that ER decreases TH (T3 and/or T4) in serum or plasma [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrate that Mt3 mRNA is reduced by thyroxine in the developing rat brain [ 18 ]. Moreover, MT mRNA and protein levels are inducible by thyroid-stimulating hormone (TSH), and their induction is considered a thyroid stress marker of autoimmune diseases [ 52 , 53 ]. Studies in mammals report that ER decreases TH (T3 and/or T4) in serum or plasma [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that gonadotropins can activate ERK signaling via both the calcium-dependent and PKCδ-dependent mechanisms and this subsequently leads to the promotion of EOC cell proliferation and migration 25 . Like the activity of gonadotropin receptors in the ovarian cells, several studies have also reported that activation of TSHR can turn on calcium and PKC signaling in thyrocytes 41 42 . Therefore, although TSHR signaling has not yet been well characterized in the ovarian cancer cells, one may speculate that it can also activate the calcium and PKC pathways, which may then contribute to at least part of the thyrostimulin-induced ERK activation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, conditional deletion of Gα q/11 in mouse thyroid resulted in hypoplastic thyroid glands and severe hypothyroidism (34). It has also been shown that Gα q/11 -PKC dependent activation in TSHR transfected papillary cancer cells (line FTC236) resulted in the upregulation of a class of redox and metal ion scavengers which are cysteine-rich proteins known as metallothioneins (MTs) (37). Studies have also shown an indirect relationship of Gα q/11 activation to thyroid peroxidase formation (34,38) and a congenital hypothyroidism phenotype (39).…”
Section: Discussionmentioning
confidence: 99%